2020
DOI: 10.3390/foods9111619
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Chicken Eggs with Vitamin K—Nutritional and Quality Improvements

Abstract: National nutrition surveys have shown that over half of all adults in Ireland, the United Kingdom (UK), and the United States of America (USA) have low vitamin K intakes. Thus, dietary strategies to improve vitamin K intakes are needed, and vitamin K biofortification of food may be one food-based approach. The primary aim of our study was to establish whether increasing the vitamin K3 content of hen feed can increase the vitamin K content of eggs, and the secondary aims were to examine the effects on hen perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In Japan, VK3 has been prohibited to use for the treatment of the vitamin K-deficient bleeding in human because of its high chemical reactivity which causes various side effects such as jaundice and so on. In rodents and domestic animals, however, VK3 is useful feed ingredient; for example, in chickens, it has been reported that VK3 feeding has a great advantage for the tissues' and eggs' MK-4 enrichment which benefits not only animals health condition but also egg quality (O'Sullivan et al, 2020). However, these findings are limited to monogastric animals.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, VK3 has been prohibited to use for the treatment of the vitamin K-deficient bleeding in human because of its high chemical reactivity which causes various side effects such as jaundice and so on. In rodents and domestic animals, however, VK3 is useful feed ingredient; for example, in chickens, it has been reported that VK3 feeding has a great advantage for the tissues' and eggs' MK-4 enrichment which benefits not only animals health condition but also egg quality (O'Sullivan et al, 2020). However, these findings are limited to monogastric animals.…”
Section: Introductionmentioning
confidence: 99%
“…The appropriate shell thickness can reduce breakage and prevent embryonic mortality by avoiding excessive water loss from the eggs, acute heat stress, and microbial invasion during incubation ( Xie et al, 2014 ). In addition, the shell thickness of eggs laid by hens fed the diet with VK3 is significantly greater than that by hens fed the diet without VK3 ( O'Sullivan et al, 2020 ). Similarly, our study found that dietary VK3 supplementation increased albumen height, shell thickness and Haugh unit in goose eggs.…”
Section: Discussionmentioning
confidence: 97%
“…Yield: 18%; yellow oil; 1 H NMR (CDCl 3 , 400 MHz): δ 1.49(s, 3H, CH�CCH 3 ), 1.80 (s, 3H, CH�CCH 3 ), 2.04(q, 2H, J = 7.2 Hz, CH 2 CH 2 ), 2.12(q, 2H, J = 7. 4 (12). Compound 12 was prepared by a similar procedure to that in the case of 4 but with compound 34 instead of compound 26 as a reactant.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Vitamin K 3 is converted to menaquinone-4 in the tissues of birds and mammals and widely used as a vitamin K additive in animal feed (Figure 1). 12 Recently, vitamin K 3 (menadione: MD) was found to inhibit the 3-chymotrypsin-like (3CL) protease of SARS-CoV-2, thereby inhibiting viral replication. 13 We predicted that vitamin K derivatives, such as vitamins K 1 and K 2 , might also exhibit anti-SARS-CoV-2 activity.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation